Geotechnical Investigation and Numerical Analysis of Rockfall in South Coast of Gunung Kidul Regency - Odhi Attabik Illiyin; Fikri Faris (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2017)
On 17th of June 2015, rockfall occurred on the South Coast at Gunung Kidul Regency taking a few casualties. The preliminary investigation results concluded that many cliffs on the South Coast are dangerous, and there is a potential that similar events might happen in the future. Therefore, geotechnical investigation in order to plan mitigation action is necessary. Field investigations, laboratory work, and numerical modeling were employed in this study, focusing on Sadranan beach where the incident happened. Rock slope stability analyses by means two-dimensional finite element in both static and seismic conditions were conducted. The investigation results show that both biological decay and wave erosion influence the rock slope instability. Moreover, the infilling material in rock joint has considerable effect on the stability of the slope. However, the results from numerical simulation suggested that potential failure was originating from the intact rock body instead of the plane of discontinuities. In the seismic condition, the slopes are more vulnerable and further mitigation action should be considered in the future.